Technologically processed and natural foods in pregnant women nutrition - Laukytė, Ieva; Vaicekauskaitė, Dalia; Dubakienė, Rūta (Acta medica Lituanica, 2014)
The objective of our study was to find out the tendencies of nutrition among pregnant women and to reveal which products, technologically processed or natural foods, were consumed more. 205 women took part in the first Lithuanian newborn cohort, PLANK-K. 62 questionnaires with 198 questions about products consumed during pregnancy were answered. In the main groups of products the majority of women consumed plant origin food. Most of the women ate bread products, grain and its products, cocoa and its products, dairy products, meat and its products. A lot of women consumed nuts and their products, various drinks, some of them ate eggs and their products. The least consumed during pregnancy were various origin fats and honey. In smaller subgroups the majority of women consumed vegetables, the minority of them ate rare meat (venison, lamb) and mixed origin fat. Speaking about technologically processed food, two groups were fit for comparison: processed meat products and canned corn. Processed meat products had big preponderance against consumption of other meat products and more than half of women chose canned corn. It is clear that in this case technologically processed food was chosen more often than non-processed food. The format of this questionnaire allows to accurately evaluate food products that mothers consume during pregnancy, but makes it harder to evaluate technologically processed and non-processed food consumption.
Keywords: pregnant women nutrition; PLANK-K; first Lithuanian birth cohort; technologically processed food; natural foods; technologically non-processed food; canned corn; technologically processed meat products